Formulasi Kosmetik Lip Balm Tabir Surya Dengan Kombinasi Kitosan dan Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) - Salmahaminati; Dyah Nuraini, Herdita; Indah Fajarwati, Febi (Chemistry Department, Universitas Islam Indonesia, 2025)
This research involved formulating lip balm using a combination of chitosan and red dragon fruit peel as active ingredients in the lip balm formula. The purpose of this research is to learning about lip balm’s physical and chemical properties, which involves adding chitosan and red dragon fruit peel, determining lip balm formulation with various concentrations of red dragon fruit peel, and understanding betalain compounds in red dragon fruit peel as antioxidants using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Based on the phytochemical screening and antioxidant test, the extract can be used as an active ingredient in cosmetics, and the antioxidant value IC50 is 0,675 mg/mL. However, this antioxidant's effectiveness is classified as low because of some environmental factors. There are 6 lip balm formulas, which are F0A, F0B, F1, F2, F3, and F4. All of the lip balm formulas have fulfilled the requirements of a lip balm product, like organoleptic test, pH test, hedonic test, and adhesive strength test. The result of the SPF test shows that lip balm formulas F0A, F0B, F1, and F2 are classified as maximum protection. Meanwhile, lip balm formulas F3 and F4 are classified as ultra protection with an SPF value >15